2022
DOI: 10.1038/s41598-022-10695-x
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of sesame extracts on seed germination of moso bamboo and identification of potential allelochemicals

Abstract: The objectives of this study were to investigate the allelopathic effects of sesame extracts of on seed germination of moso bamboo, and to isolate and identify the potential allelochemicals. A factorial design with three organs (root, stem and leaf) and five concentrations (0, 25, 50, 75 and 100 mg mL−1) was carried out. Seeds of moso bamboo were soaked in sesame extracts to investigate their germination and growth. The allelochemicals were isolated and identified using the high performance liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…They had reported a significant decrease in seed germination and seedling growth (root and shoot length and weight). An analogous phytotoxic effect on germination and seedling growth of the medicinal and aromatic plant studied by Zubay et al, 2021, allelopathic effects of sesame extracts on seed germination of bamboo observed by Zhao et al (2022), Senna garrettiana leaves extract to inhibit the growth of Lepidium sativum L. and Echinochloa crus-Galli (L.) studied by Krumsri et al 2022., andAragão et al, (2017) found that the sesquiterpene in Lepidaploa rufogrisea had a phytotoxic effect on weeds. In their investigation, Nega and Gudeta (2019) reported that allelochemicals in the Eucalyptus globulus plant components severely affect teff and barely seed germination and early seedling growth.…”
Section: Resultsmentioning
confidence: 87%
“…They had reported a significant decrease in seed germination and seedling growth (root and shoot length and weight). An analogous phytotoxic effect on germination and seedling growth of the medicinal and aromatic plant studied by Zubay et al, 2021, allelopathic effects of sesame extracts on seed germination of bamboo observed by Zhao et al (2022), Senna garrettiana leaves extract to inhibit the growth of Lepidium sativum L. and Echinochloa crus-Galli (L.) studied by Krumsri et al 2022., andAragão et al, (2017) found that the sesquiterpene in Lepidaploa rufogrisea had a phytotoxic effect on weeds. In their investigation, Nega and Gudeta (2019) reported that allelochemicals in the Eucalyptus globulus plant components severely affect teff and barely seed germination and early seedling growth.…”
Section: Resultsmentioning
confidence: 87%
“…[52] A factorial experimental design including three organs (root, stem and leaf) and five concentrations (0, 25, 50, 75 and 100 mg/mL) was performed to evaluate the allelopathic effect of sesame extract to moso bamboo seeds. [53] The results showed that the aqueous extract of sesame led to delayed germination and growth of moso bamboo seeds. According to the previous methods, 4 gradients (0, 5, 10, 15 mg/mL) were desgined for allelopathy determination and showed effctive allelopathic inhibition on radish seed.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine the allelopathic effects of Eucalyptus globulus leaves in five concentrations (5, 10, 15, 20, and 25 g/L) on seed germination and seedling growth of eggplant [52] . A factorial experimental design including three organs (root, stem and leaf) and five concentrations (0, 25, 50, 75 and 100 mg/mL) was performed to evaluate the allelopathic effect of sesame extract to moso bamboo seeds [53] . The results showed that the aqueous extract of sesame led to delayed germination and growth of moso bamboo seeds.…”
Section: Discussionmentioning
confidence: 99%
“…These differential effects of aqueous extracts from various plant organs on recipient plant growth within intercropping systems underscore the existence of varying allelopathic potentials among different plant organs. 36 It is essential to recognize that the relatively high experimental concentrations employed in our study were selected for specific scientific purposes. Our primary aim was to elucidate potential chemical reactions under controlled conditions, thereby enhancing our comprehension of the behavior of bioactive compounds.…”
Section: ■ Discussionmentioning
confidence: 99%